BAX 2015 : Best American Experimental Writing - Damiani, Jesse; Abramson, Seth, 1976-; Kearney, Douglas (Book collections on Project MUSE., 2015)
BAX 2015 is the second volume of an annual literary anthology compiling the best experimental writing in poetry, fiction, and creative nonfiction. This year's volume, guest edited by Douglas Kearney, features seventy-five works by some of the most exciting American poets and writers today, including established authors--like Dodie Bellamy, Anselm Berrigan, Thomas Sayers Ellis, Cathy Park Hong, Bhanu Kapil, Aaron Kunin, Joyelle McSweeney, and Fred Moten--as well as emerging voices. Best American Experimental Writing is also an important literary anthology for classroom settings, as individual selections are intended to provoke lively conversation and debate.